2019
DOI: 10.3390/ijms20030477
|View full text |Cite
|
Sign up to set email alerts
|

Self-Seeding Microwells to Isolate and Assess the Viability of Single Circulating Tumor Cells

Abstract: The availability of viable tumor cells could significantly improve the disease management of cancer patients. Here we developed and evaluated a method using self-seeding microwells to obtain single circulating tumor cells (CTC) and assess their potential to expand. Conditions were optimized using cells from the breast cancer cell line MCF-7 and blood from healthy volunteers collected in EDTA blood collection tubes. 43% of the MCF-7 cells (nucleus+, Ethidium homodimer-1-, Calcein AM+, α-EpCAM+, α-CD45-) spiked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…VyCAP microsieves collect CTC by their relative size and rigidity, allowing for the detection of both EpCAM positive and negative cells (1)(2)(3). In addition, modified versions of these filters may allow isolation of single CTC for genomic analysis, or to perform functional tests in captured CTC (14)(15)(16)(17)(18). In this study we looked into the capability of VyCAP microsieves to filter the DLA product of NSCLC patients to enumerate CTC and compare the CTC counts per patient with those of CellSearch.…”
Section: Introductionmentioning
confidence: 99%
“…VyCAP microsieves collect CTC by their relative size and rigidity, allowing for the detection of both EpCAM positive and negative cells (1)(2)(3). In addition, modified versions of these filters may allow isolation of single CTC for genomic analysis, or to perform functional tests in captured CTC (14)(15)(16)(17)(18). In this study we looked into the capability of VyCAP microsieves to filter the DLA product of NSCLC patients to enumerate CTC and compare the CTC counts per patient with those of CellSearch.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Recently we have shown that cells from different cancer cell lines can be isolated from the microwells and expanded. 24 In Fig. S3a and b † we demonstrate that individual CHO cells can be individually recovered from the microwell and expanded.…”
Section: Quantification Of Antibody Secreted By Cellsmentioning
confidence: 78%
“…Antigens secreted by single PC cells were used to demonstrate the potential of the method. Although single-cell assays can be performed with ELISA or ELISPOT-based methods, our presented single-cell approach provides four advantages over traditional approaches: (a) the ability to handle small samples with few cells; (b) the ability to measure the secreted PSA proteins because they are immunocaptured by the membrane in the vicinity of the cells without being diluted in the culture supernatant; (c) the ability to investigate the cellular heterogeneity of 6400 viable single cells in parallel; and (d) the possibility to retrieve cells of interest for further analysis [ 13 , 16 ]. Because of the hydrodynamic single cell distribution principle, we can efficiently capture 1 cell/well (>90%) and cells remained viable for days.…”
Section: Discussionmentioning
confidence: 99%